Super Learning Model and Cognitive Achievement Among First Grade Intermediate Students - Adnan Mayouf Ali (Academia Open, 2025)
General Background: History education is increasingly expected to move beyond memorization by promoting analytical thinking and meaningful engagement with historical contexts. Specific Background: The FATA Super Learning Model, which integrates focusing, activity-based exploration, guided training, and applied learning, has been suggested as an approach that can strengthen students’ cognitive and analytical skills, yet empirical evidence in early secondary history education is still limited. Knowledge Gap: Research examining teachers’ perceptions of the model’s effectiveness and its direct influence on cognitive achievement among middle-school students remains scarce. Aims: This study analyzes the effectiveness of the FATA model in enhancing cognitive achievement, historical reasoning, and classroom interaction among first-grade intermediate students in Iraq. Results: Responses from 50 history teachers show strong agreement that the model deepens understanding, increases motivation, improves critical analysis, strengthens the ability to link past and present, and enhances active participation, although challenges such as limited training, resource constraints, and insufficient institutional support were noted. Novelty: The study offers one of the earliest systematic evaluations of the FATA model within Iraqi middle-school settings, combining quantitative and qualitative data from practitioners. Implications: The findings underline the importance of structured training, curriculum alignment, and stronger institutional support to ensure effective and sustainable implementation of the model in history classrooms.Highlight : Highlights the model’s role in strengthening students’ deep understanding of historical events. Emphasizes improved motivation and active engagement during history learning. Underscores the model’s contribution to linking past events with present-day contexts. Keywords : Super Learning, FATA Model, Teaching History, Cognitive Achievement, Critical Thinking